Appearance and Social Inequalities: Physical Attractiveness as a Part of Occupation-Congruent Appearance - Sarpila, Outi; Koivula, Aki; Kukkonen, Iida (SAGE Publications, 2025)
Appearance-based inequalities are gaining increasing interest in sociology. This article is the first to systematically examine the extent to which attractiveness is linked to culturally shared ideas of representatives of different occupations. We conceptualise these cultural expectations as ‘occupation-congruent appearance’. To understand the gendered dynamics between attractiveness and looking ‘congruent’, we analyse large-scale photograph data representing a heterogeneous group of different occupations (n = 1411), including population-level ratings on those photographs (n = 3456). We find that for both men and women, attractiveness is generally associated with an increase in perceived occupation-congruent appearance. However, this association is gendered, so the differences between occupational categories are greater for men than for women. Therefore, we argue that attractiveness can magnify appearance-based status differences, particularly among men. The research opens new perspectives to examine appearance and inequalities, not only from the perspective of looking attractive, but also through looking congruent.